Nasopharyngeal Microbiomes in Donkeys Shedding Streptococcus equi Subspecies equi in Comparison to Healthy Donkeys - Zhu, Yiping; Chen, Shulei; Yi, Ziwen; Holyoak, Reed; Wang, Tao; Ding, Zhaoliang; Li, Jing (Frontiers in Veterinary Science, 2021)
Streptococcus equi subsp. equi (S. equi) is the primary pathogen causing strangles, a highly infectious disease that can affect equids including donkeys of all ages. It can persistently colonize the upper respiratory tract of animals asymptomatically for years and serve as a source of infection. Strangles outbreaks have been reported in the donkey industry in China multiple times in the last few years and poses a great threat to health, production, and the welfare of donkeys. Nasopharyngeal swab samples for culture and PCR are used widely in strangles diagnosis with reliable accuracy. Additionally, microbiomes have been considered to critically affect and reflect animal health. Therefore, the microbiomes from the equid nasopharynx may provide insights of the health of the upper respiratory tract in animals. So far, there has been no study focusing on the nasopharyngeal microbiome in healthy donkeys, nor on donkeys shedding S. equi. This study aimed to compare nasopharyngeal microbiomes in healthy and carrier donkeys using 16S rRNA gene sequencing. Nasopharyngeal samples were obtained from 16 donkeys recovered from strangles (group S) and 14 donkeys with no history of having strangles (group H). Of those sampled, 7 donkeys were determined to be carriers with positive PCR and culture results in group S and all 14 donkeys were free of strangles based on negative results of PCR and culture. Samples from these 21 donkeys were used for microbial analysis. Totally 2291 OTUs were identified and the nasopharyngeal microbiome was significantly different between the two groups. Furthermore, carrier donkeys had less rich OTUs as opposed to healthy donkeys. At the phylum level, Proteobacteria in carrier donkeys was predominantly higher in the S. equi carrier donkeys than in healthy donkeys (P<0.01), while Firmicutes and Actinobacteria were significantly lower in the S. equi carrier donkeys than in healthy donkeys (P<0.05). At the genus level, Nicoletella was detected in the upper respiratory tract of donkeys for the first time and dominated in carrier donkeys. We conclude that nasopharyngeal microbiomes could be distinct from other parts of upper respiratory tract and S. equi carrier donkeys still exhibit microbial dysbiosis despite of lacking clinical signs.